CD8+ T Cell Co-Expressed Genes Correlate With Clinical Phenotype and Microenvironments of Urothelial Cancer - Wang, Yutao; Yan, Kexin; Lin, Jiaxing; Liu, Yang; Wang, Jianfeng; Li, Xuejie; Li, Xinxin; Hua, Zhixiong; Zheng, Zhenhua; Shi, Jianxiu; Sun, Siqing; Bi, Jianbin (Frontiers in Oncology, 2020)
Abstract Purpose: To identify immune-related co-expressed genes that promote CD8+ T cell infiltration in bladder cancer, and to explore the interactions among relevant genes in the tumor microenvironment. Method: We obtained bladder cancer gene matrix and clinical information data from TCGA, GSE32894 and GSE48075. The “estimate” package was used to calculate tumor purity and immune score. The CIBERSORT algorithm was used to assess CD8+ T cell proportions. Weighted gene co-expression network analysis was used to identify the co-expression modules with CD8+ T cell proportions and bladder tumor purity. Subsequently, we performed correlation analysis among angiogenesis factors, angiogenesis inhibitors, immune inflammatory responses, and CD8+ T cell related genes in tumor microenvironment . Results: A CD8+ T cell related co-expression network was identified. Eight co-expressed genes (PSMB8, PSMB9, PSMB10, PSME2, TAP1, IRF1, FBOX6, ETV7) were identified as CD8+ T cell-related genes that promoted infiltration of CD8+ T cells, and were enriched in the MHC class I tumor antigen presentation process. The proteins level encoded by these genes (PSMB10,PSMB9,PSMB8,TAP1,IRF1 and FBXO6) were lower in the high clinical grade patients, which suggested the clinical phenotype correlation both in mRNA and protein levels. These factors negatively correlated with angiogenesis factors and positively correlated with angiogenesis inhibitors. PD-1 and PD-L1 positively correlated with these genes which suggested PD-1 expression level positively correlated with the biological process composed by these co-expression genes. In the high expression group of these genes, inflammation and immune response were more intense, and the tumor purity was lower, suggesting that these genes were immune protective factors that improved the prognosis in patients with bladder cancer. Conclusion: These co-expressed genes promote high levels of infiltration of CD8+ T cells in an immunoproteasome process involved in MHC class I molecules. The mechanism might provide new pathways for treatment of patients who are insensitive to PD-1 immunotherapy due to low degrees of CD8+ T cell infiltration.